Single‐Molecule Counting Coupled to Rapid Amplification Enables Detection of α‐Synuclein Aggregates in Cerebrospinal Fluid of Parkinson's Disease Patients. Issue 21 (7th April 2021) - Bhumkar, Akshay; Magnan, Chloe; Lau, Derrick; Jun, Eugene Soh Wei; Dzamko, Nicolas; Gambin, Yann; Sierecki, Emma
Abstract: α‐Synuclein aggregation is a hallmark of Parkinson's disease and a promising biomarker for early detection and assessment of disease progression. The prospect of a molecular test for Parkinson's disease is materializing with the recent developments of detection methods based on amplification of synuclein seeds (e.g. RT‐QuIC or PMCA). Here we adapted single‐molecule counting methods for the detection of α‐synuclein aggregates in cerebrospinal fluid (CSF), using a simple 3D printed microscope. Single‐molecule methods enable to probe the early events in the amplification process used in RT‐QuIC and a precise counting of ThT‐positive aggregates. Importantly, the use of single‐molecule counting also allows a refined characterization of the samples and fingerprinting of the protein aggregates present in CSF of patients. The fingerprinting of size and reactivity of individual aggregate shows a unique signature for each PD patients compared to controls and may provide new insights on synucleinopathies in the future. Abstract : A new single‐molecule method was established for the detection of α‐synuclein fibrils, a promising biomarker of Parkinson's disease (PD). Individual ThT(+) aggregates were fingerprinted and amplified to improve detection limits by 3 orders of magnitude, compared to direct detection. A difference of behaviour was detected between PD and control samples.